2012
DOI: 10.1063/1.4766898
|View full text |Cite
|
Sign up to set email alerts
|

On stability of collisional coupling between relativistic electrons and ions in hot plasmas

Abstract: Abstract. The collisional coupling of relativistic electrons and non-relativistic ions in hot plasmas has been analysed. It is found that relativistic effects produce a new feature: while the condition T e < 3T i guarantees a stable collisional coupling between electrons and ions in low-temperature plasmas, relativistic effects shift the upper T e /T i boundary of stability to higher values. Moreover, for sufficiently high temperatures, T e,i > 75 keV, collisional decoupling between relativistic electrons and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This process is significant only if and are different. In this case, the contribution from is negligible, and the energy exchange can be explicitly calculated with the relativistic Jüttner-Maxwellian distribution of electrons and the classical Maxwellian distribution of ions [18], (in somewhat different form it was obtained also in [17]).…”
Section: The Equations For Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is significant only if and are different. In this case, the contribution from is negligible, and the energy exchange can be explicitly calculated with the relativistic Jüttner-Maxwellian distribution of electrons and the classical Maxwellian distribution of ions [18], (in somewhat different form it was obtained also in [17]).…”
Section: The Equations For Momentsmentioning
confidence: 99%
“…In addition, fully relativistic hydrodynamic has already been developed [17]. At the same time, the plasma generated in laboratory, for example in fusion devices, does not require such a formalism and can be well described without refence to the Lorentz invariance [18][19][20][21]. The present paper deals with the case of quite practical needs and the results obtained here can be easily implemented in any transport code.…”
Section: Introductionmentioning
confidence: 99%
“…The first one appears due to a reduction of the contribution from the bulk of the distribution function and prevails in the low-temperature range, T e < 10 keV, leading to a decrease in transport coefficients (note that the slope in figure 1(a) is almost the same for all transport coefficients in this temperature range). A decrease in the bulk contribution is caused by the specific feature of the Maxwell-Jüttner distribution function and can be estimated from C MJ equation (5). The second effect is caused by a broadening of the energy range of contributing electrons and the shift of the maximum of the integrand into higher energies, and this leads to an increase in the transport coefficients with temperature.…”
Section: Comparison Of Relativistic and Non-relativistic Radial Fluxesmentioning
confidence: 99%
“…These effects appear due to the macroscopic features of the relativistic thermodynamic equilibrium given by the Maxwell-Jüttner distribution function [1,4]. An example of such effects provided by the Maxwell-Jüttner distribution function is given in a recent paper [5], where the stability criterion for collisional heat transfer from hot electrons to ions with respect to the Coulomb decoupling is studied and it is found that relativistic effects lead to qualitative changes in stability criteria. While in non-relativistic plasmas criterion is given by T e /T i < 3, relativistic effects makes it temperature-dependent and for T e,i > 75 keV the collisional coupling between electrons and ions becomes absolutely stable.…”
Section: Introductionmentioning
confidence: 99%
“…These effects appear due to the macroscopic features of the relativistic thermodynamic equilibrium given by the Maxwell-Jüttner distribution function [1,4]. An example of such effects provided by the Maxwell-Jüttner distribution function is given in a recent paper [5], where the stability criterion for collisional heat transfer from hot electrons to ions with respect to the Coulomb decoupling is studied and it is found that relativistic effects lead to qualitative changes in stability criteria. While in non-relativistic plasmas criterion is given by T e /T i < 3, relativistic effects makes it temperature-dependent and for T e,i > 75 keV the collisional coupling between electrons and ions becomes absolutely stable.…”
Section: Introductionmentioning
confidence: 99%